2017
DOI: 10.1039/c7dt03120c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Ca2+complexing properties of isosaccharinate and gluconate – is gluconate a reliable structural and functional model of isosaccharinate?

Abstract: The calcium complexation and acid-base properties of α-d-isosaccharinate (Isa) in neutral and in (hyper)alkaline solutions have been investigated via potentiometric titrations, multinuclear NMR, ESI-MS and quantum chemical calculations. Isa is the primary alkaline degradation product of cellulose, and may be present in radioactive waste repositories and therefore, it could contribute to the mobilization of radioactive nuclei. Because of its limited availability, d-gluconate (Gluc) is commonly used as a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…10 They concluded that both Ca 2+ and Eu 3+ form complexes with ISA via the carboxylic as well as the αand γ-hydroxy groups. Similar results were obtained for Ca 2+ by Dudás et al 26 Apart from the identification of the carboxylic, and αand γ-hydroxy groups as coordinating functionalities, their NMR results showed that the β-hydroxy group is not involved. Tasi et al…”
Section: Structural Properties Of Uo 2 2+supporting
confidence: 85%
See 2 more Smart Citations
“…10 They concluded that both Ca 2+ and Eu 3+ form complexes with ISA via the carboxylic as well as the αand γ-hydroxy groups. Similar results were obtained for Ca 2+ by Dudás et al 26 Apart from the identification of the carboxylic, and αand γ-hydroxy groups as coordinating functionalities, their NMR results showed that the β-hydroxy group is not involved. Tasi et al…”
Section: Structural Properties Of Uo 2 2+supporting
confidence: 85%
“…24 The pK a value of the carboxylic group is 3.27 while the deprotonation of alcohol functionalities is expected to occur above pH 12. 23,25,26 However, the acidity of alcohol functionalities is expected to increase upon their interaction with Lewis acidic metal centers. 23,27 The previously mentioned impact of ISA on the sorption and solubility was gen-erally traced back to the formation of strong complexes in which the hydroxyl groups of the ligand in addition to the carboxylic group play a crucial role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they form weak binary complexes with Ca of the type CaL + in acidic to weakly alkaline conditions, several studies available in the literature provide evidence on the formation of stable complexes of ISA/GLU with Ca in hyperalkaline pH conditions, which involve the deprotonation (besides the carboxylic group) of at least one of the alcohol groups in those ligands [e.g. CaLH -1 (aq) or Ca 3 L 2 H -4 (aq)] (Hummel et al, 2005;Pallagi et al, 2014;Dudas et al, 2017;Kutus et al, 2020). A similar effect was suggested by Jo and co-workers for C-S-H-ISA surface complexes based on molecular dynamics calculations (Jo et al, 2022).…”
Section: Comparison With Sorption Data Available In the Literaturementioning
confidence: 99%
“…The ISA isomers are major degradation products of cellulose (Glaus et al, 1999;Van Loon et al 1999, Rout et al, 2015, Shaw 2013. Most of the complexation data on α-ISA and analogues, such as gluconate (Dudás et al, 2017), have been measured at high pH, e.g. pH = 13.3 in Tits et al (2005).…”
Section: Adsorption Of Eu(iii) On Cox Clay Rockmentioning
confidence: 99%